About the stratigraphic position of the Lower Aptian Roloboceras hambrovi (Ammonoidea) level - Conte Gabriel; Tronchetti Guy; Moullade Michel; Ropolo Pierre (Carnets de Géologie, 2008)
In the stratotype of the Lower Aptian substage the position of the assemblage that includes Roloboceras spp. and Megatyloceras spp. has been clearly established as being in the middle part of the upper Bedoulian. Some authors have erected this horizon as a subzone, or even a zone, with R. hambrovi as species-index. In other areas (southern England, eastern Spain, the Ardèche in southeastern France), where taphonomic conditions are not always as favourable as they are in the stratotype, the level at which this assemblage occurs seems to be confined to the upper part of the lower Bedoulian. Various hypotheses are considered in an attempt to explain this divergence.